Financial Risk Tolerance dan Sikap Keuangan terhadap Keputusan Investasi Deposito dengan Financial Literacy sebagai Variabel Moderasi - Damayanti, Alpina; Anggriani, Rini; Sidharta, Raden Bagus Faizal Irany; Alpiansah, Restu; Saputra, Sahdan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study aims to analyze the effect of financial risk tolerance and financial attitude on deposit investment decisions with financial literacy as a moderating variable. The research object is Micro, Small, and Medium Enterprises (MSMEs) actors in East Lombok Regency. This study uses a quantitative approach with a survey method through the distribution of questionnaires to MSME actors. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The research results indicate that financial risk tolerance and financial attitude have a positive and significant effect on deposit investment decisions. However, financial literacy is unable to moderate the influence of financial risk tolerance or financial attitude on investment decisions. These findings suggest that in low-risk investment instruments such as deposits, psychological and behavioral factors are more dominant compared to financial knowledge aspects. This study provides a theoretical contribution to the study of behavioral finance by emphasizing that the role of financial literacy is contextual.